2014
DOI: 10.4238/2014.september.12.8
|View full text |Cite
|
Sign up to set email alerts
|

Association between a functional variant in microRNA-27a and susceptibility to colorectal cancer in a Chinese Han population

Abstract: ABSTRACT. Polymorphisms in pri-, pre-, and mature-microRNAs (miRNAs) have been proposed to be associated with various human cancers. Common single nucleotide polymorphisms (SNPs) in miRNA genes can influence the maturation of miRNAs or miRNA-mediated transcriptional regulation. Through genotyping the rs895819 SNP in 254 colorectal cancer (CRC) patients and 238 healthy controls by polymerase chain reaction-restricted fragment length polymorphism, a case-control study was performed to investigate a possible asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
3
26
1
Order By: Relevance
“…Recently, numerous miRNA sequence variations have been implicated in CRC (Lv et al, 2013;Cao et al, 2014). However, the results of many such studies are conflicting and inconclusive.…”
Section: Mirna Snps and Their Association With Crcmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, numerous miRNA sequence variations have been implicated in CRC (Lv et al, 2013;Cao et al, 2014). However, the results of many such studies are conflicting and inconclusive.…”
Section: Mirna Snps and Their Association With Crcmentioning
confidence: 99%
“…After screening of titles and abstracts, 38 studies clearly irrelevant to the subject of interest were excluded, and from the remaining 40 publications, 18 reviews were removed. Finally, after screening of method sections, 22 epidemiological investigations focusing on the importance of miRNA-related SNPs in CRC susceptibility were retained [Zhan et al, 2011;Chen et al, 2012;Hezova et al, 2012;Min et al, 2012;Ryan et al, 2012;Zhang et al, 2012;Zhu et al, 2012;Chae et al, 2013;Gao et al, 2013;Lv et al, 2013;Ma et al, 2013;Vinci et al, 2013;Cao et al, 2014;Hu et al, 2014;Li et al, 2013Li et al, , 2014 (for unpublished results of Chen, 2013); Mao et al, 2014;Oh et al, 2014;Parlayan et al, 2014;Wang et al, 2014a,b;Dikaiakos et al, 2015; miRNA = microRNA; SNP = single nucleotide polymorphism; HB = hospital-based study; PB = populationbased study; PCR-RFLP = polymerase chain reaction-restriction fragment length polymorphism; PCR-LDR = polymerase chain reaction-ligase detection reaction; HRM = high-resolution melting. 1 Unpublished data recorded by Chen (2013), included in the review authored by Li et al (2014).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…However, Cao et al. reported that genotypes AG and GG had a significantly increased risk of developing CRC compared to AA carriers in Chinese. For this, in order to address the role of rs895819 in susceptibility to CRC, we genotyped the locus in 508 CRC patients and 562 healthy check‐up individuals using TaqMan genotyping polymerase chain reaction (PCR) system, and examined the possible association between them.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, it has been shown that microRNAs (miRNAs) play a critical role in a variety of diseases, especially in cancers (Wang et al, 2012;Cao et al, 2014;Qi et al, 2015). A miRNA is a type of non-coding single-stranded RNA, usually between 18 to 24 bp long.…”
Section: Introductionmentioning
confidence: 99%